Ferrous sulfate, but not iron polymaltose complex, aggravates local and systemic inflammation and oxidative stress in dextran sodium sulfate-induced colitis in rats - Toblli JE; Cao G; Angerosa M (Dove Medical Press, 2015)
Jorge E Toblli, Gabriel Cao, Margarita Angerosa Laboratory of Experimental Medicine, Hospital Alemán, School of Medicine, University of Buenos Aires, Buenos Aires, Argentina Background and aims: Iron deficiency is common in inflammatory bowel disease, yet oral iron therapy may worsen the disease symptoms and increase systemic and local oxidative stress. The aim of this study was to compare the effects of oral ferrous sulfate and iron polymaltose complex on inflammatory and oxidative stress markers in colitic rats.Methods: Animals were divided into four groups with ten animals each. Rats of three groups received dextran sodium sulfate to induce colitis and animals of two of these groups received 5 mg iron/kg of body weight a day, as ferrous sulfate or iron polymaltose complex, for 7 days. Gross colon anatomy, histology of colon and liver, stainings of L-ferritin, Prussian blue, hepcidin, tumor necrosis factor-α, and interleukin-6, as well serum levels of liver enzymes, inflammatory markers, and iron markers, were assessed.Results: Body weight, gross anatomy, crypt injury and inflammation scores, inflammatory parameters in liver and colon, as well as serum and liver hepcidin levels were not significantly different between colitic animals without iron treatment and colitic animals treated with iron polymaltose complex. In contrast, ferrous sulfate treatment caused significant worsening of these parameters. As opposed to ferrous sulfate, iron polymaltose complex caused less or no additional oxidative stress in the colon and liver compared to colitic animals without iron treatment.Conclusion: Iron polymaltose complex had negligible effects on colonic tissue erosion, local or systemic oxidative stress, and local or systemic inflammation, even at high therapeutic doses, and may thus represent a valuable oral treatment of iron deficiency in inflammatory bowel disease. Keywords: preclinical, oral iron treatment, tolerability, colonic tissue erosion, inflammatory bowel disease